Functional capacity, independence and home affordances of premature children attending daycare centers - Marcela Tamiasso Vieira; Joselici da Silva; Jaqueline da Silva Frônio
Abstract Introduction: Child development is the result of the interaction between biological and environmental factors. Objective: The aim of this study is to evaluate and compare the Functional Capacity, Independence and Home Affordances Level of Stimulation of premature children between 18 and 42 months, attending or not daycare centers. Methods: Cross-sectional study with a convenience sample of 26 premature children between 18 and 42 months, paired and divided into two groups: attending (study group) and not attending daycare centers (control group). Data was collected from the questionnaires AHEMD-SR, PEDI and an identification questionnaire. Data analysis was performed by descriptive statistics, and Chi-square, Fisher, Mann-Whitney and Univariate Analysis tests, considering the level of significance of α = 0.05 and tendency of differentiation when α < 010. Results: There was a significant difference in the AHEMD-SR`s Variety of Stimulation (p = 0.036), higher in the control group, and tendency in the Gross Motor Toys (p = 0.086), more available in the study group. In PEDI, there was significant difference in Self-care (p = 0.045) and tendency of differentiation in Mobility (0.068), both of the Caregiver Assistance part (greater to the study). The sample showed low stimulation opportunities regarding Fine and Gross Motor Toys and high percentages of delay in Functional Skills (Mobility) and Independence (Self Care and Mobility), especially in the control group. Conclusion: Daycare centers seem to positively affect the Functional Capacity and Independence in premature children between 18 and 42 months.